SPECIALIZED MAPPING OF CRUSTAL FAULT ZONES. PART 1: BASIC THEORETICAL CONCEPTS AND PRINCIPLES - K. Zh. Seminsky (Геодинамика и тектонофизика, 2015)
Long-term studies of shear zones have included collection of data on fractures showing no indication of displacement which are termed as 'blank' fractures. A method aimed at mapping fault structures and stress fields has been developed on the basis of results of paragenetic analysis of measurements of abundant fractures. The method is termed as 'specialized mapping', firstly, due to its specific structural goal so that to distinguish it from the conventional geological mapping of regions in nature, and, secondly, because of the specific procedure applied to refer to fractures as references to decipher fault-block patterns of natural regions. In Part 1, basic theoretical concepts and principles of specialized mapping are described. Part 2 is being prepared for publication in one of the next issues of the journal; it will cover stages of the proposed method and describe some of the cases of its application.In terms of general organizational principles, specialized mapping is similar to other methods based on structural paragenetic analysis and differs from such methods in types of paragenesises viewed as references to reveal crustal fault zones. Such paragenesises result from stage-by-stage faulting (Fig 2 and Fig. 7) during which stress fields of the 2nd order are regularly changeable within the shear zone. According to combined experimental and natural data, a complete paragenesis of fractures in the shear zone includes a major (1st order) fault plane and fractures of other seven types, R, R’, n, n’, t, t’ and T (2nd order) (Fig. 4 and Fig 8). At the fracture level, each of them corresponds to a paragenesis including three nearly perpendicular systems of early ruptures (Fig. 1), which are based on two classical patterns of conjugated fractures, one of which is consistent with the position of the fault plane (Fig. 3). Taking into account that strike-slip, reverse and normal faults are similar in terms of mechanics (i.e. they are formed due to shearing), standard patterns of fractures systems for their impact zones are members of the above described paragenesis of faults and fractures, which is spatially oriented in such a way that its position and displacements along Y-shears are correspondent to the right- or left-lateral strike-slip faults and also to normal and reverse faults with different dip angles. Under this approach, it has become possible to construct standard circle diagrams / patterns, each containing a complete set of fracture systems of one of the main types of fault zones (Fig. 6). In the process of specialized mapping, the patterns are compared with diagrams based on mass crustal fracture measurements taken on sites in the regions of studies. This procedure yields local solutions showing a presence of fault zones of specific types and spatial orientations; such solutions are shown as points at the corresponding sites on the schematic map of the territory under study, and points with similar paragenesises are then connected by lines so that to outline the boundaries of the revealed fault zones.Besides construction of a schematic map of a fault structures, specialized mapping provides for identification of stress fields wherein elements of such a fault structure has formed or activated at some stages. With this goal, the identified fault zones are classified by ranks. At the first phase of such analysis, types and orientations of all the initial local solutions are compared with types and orientation of the members of the ‘ideal’ paragenesis of the 2nd order, which corresponds to a strike-slip, reverse (thrust) or normal fault (Fig. 8). This procedure reveals solutions showing the presence of fault zones varying in types and classified in the higher rank, which correspond to the regional stress field known form the history of the region under study. Such regional solutions are used as a basis for further iterations with reference to ‘ideal’ fault paragenesises, until possibilities to classify the fault zones into the fault networks of some specific types are exhausted. A few (typically, three to four) remaining solutions, showing orientations of the fault zone and the dynamic setting of its formation, are indicative of the lowest (regional or geostructural) level of the process of destruction in the region under study. Their simultaneous development is impossible, and therefore they correspond to different stages of faulting in the territory under study. Indirect (statistical) indicators of frequencies and angle ratios of fault systems and direct (apriory) information are used to determine ages and to reveal evolutional stages in time. At a final stage of specialized mapping, a reversed procedure provides for construction of schematic maps of fault zones for every main stage of formation of the structure under study. With this goal, faults that occurred or activated in a specified stress field are distinguished from the fault network.In addition to the paragenesis principle applied to reveal fault zones and the evolution-in-time principle used to reveal stages of structure formation, the method of specialized mapping employs statistical methods of data collection and processing, and its application is consistent and computerized through all the work stages. It provides for solution of problems dealing with ‘blank’ fracturing with account of seemingly chaotic fracture patterns, local initial observations, uncertainties of age relations, impacts of structural and material inhomogeneities, and long timelines of statistical data collection and processing. In view of the above, specialized mapping can be proposed as one of the most efficient methods of studying the fault structure of the Earth’s crust.Part 2 will describe cases of application of the proposed method to map fault zones and to identify fault types and stress fields varying in ages in the regions of faulting, including areas wherein rocks are poorly outcropped. The main results of application of the proposed method of specialized mapping is schematic maps of fault zones, showing the fault zones that were active at various stages of formation of the structure under study. Such maps can be used as a basis for finding solutions to the main problems of endo- and exogeodynamics as well as for assurance of structural control over mineral deposits associated with faulting.